Geometria nos currículos dos anos finais do ensino fundamental: uma análise à luz dos modelos teóricos de Josep Gascón - Camilo, Christiane Molina (2007)
The aim of the present work is to analyze the curricula prescription in the Geometry teaching nowadays, taking as a base theorical models such as Euclidianism, Almost-empiric and Construtivism made by teacher and researcher Josep Gascón. In this research, we aim to answer the following questions: How can the theorical models called Euclidianism, Almost-empiric and Construtivism be identified in the particular route of Geometry teaching and what is its implication to the curricula organization on Basic Teaching? Analyzing the curricula prescription to the teachings of Geometry nowadays, what is its base and how are they being worked effectively in the classroom? To have this work developed, a biographical and documental research was organized and analyzed through books which were used in the 1930 s and the 1970 s up to the present moment. On a second moment a study was made about how the present curricula is being developed in the classroom, in the final four years of the Elementary school, of two school located in the cities of São Bernardo do Campo and Guarulhos. Six teachers answered a questionnaire where they reported the work which was developed in Geometry in 2005. The study was complemented with the analysis of the planning documents produced by the teachers on the same year. The results show that the theorical models of Gascón can be identified and that probably influenced the teaching of Geometry in different analyzed decades. On documents and books a significant presence of Euclidianism was noticed even before The Moviment of Modern Mathematics; the emergence of an Almost-empiric feature as in the project Experimental Geometry in the 70 s and that still nowadays remains in the curricula, and also the small presence of a Construtivist perspective in learning-teaching experience of Geometry. Even though there are indications of Construtivist perspective in the National Curricular Parameters, they are not explicit. It is still observed that although teachers refer to these documents, an Almost-empiric feature in the teachings of Geometry is adopted